Disposal is Not Free : Fiscal Instruments to Internalize the Environmental Costs of Solid Waste - Matheson, Thornton (IMF Working Papers; Working Paper ;, 2019)
This paper provides an overview of global solid waste generation, its environmental costs, and fiscal instruments that can be used to encourage waste reduction and finance proper disposal. Countries-especially island nations--struggle to manage an ever-increasing volume of solid waste, generation of which is projected to exceed 2 billion tons a year by 2025. Although solid waste management is usually relegated to subnational governments, externalities from inadequate management, which include greenhouse gas emissions and ocean plastic pollution, reach global scale. National governments thus play a critical role in creating incentives for waste minimization and ensuring adequate resources for proper waste management. This paper evaluates potential fiscal instruments to achieve these goals, particularly in developing country policy environments.